Some Questions of The Organization of Recreational Tourism in The Desert Zone (By the Example of The Bukhara Region) (Eurasian Journal of History, Geography and Economics, 2023)
This article discusses some issues of organizing recreational tourism in the desert zone. The article analyzes the possibilities of recreational tourism on the example of the Bukhara region. Information is also provided on the objects of recreational tourism in the Bukhara region